Reexamining the international importance of languages - Moreno Fernández, Francisco; Álvarez Mella, Héctor (HCIAS working papers on Ibero-America, 2022)
This paper addresses the scientific and social interests in the comparative analysis of the international importance of language. In order to classify the different approaches to this analysis according to the criteria on which they are based, the following typology is proposed: the perception of importance, the estimation of importance, and the calculation of complex indexes. Secondly, the study provides an update to the international language index and its indicators for the year 2020. Finally, the results are analyzed and compared with those of the previous indexes. The analysis provides a picture of the plural and polycentric constellation of international languages including Spanish and Portuguese, defined by their areas of influence and spread.
Gesehen am 22.02.2022